The Effect of Place-Based Education Integrated Project Studies on Students’ Problem-Solving and Social Skills - Akbaş, Yavuz; Çakmak, Safiye (Asian Journal of Education and Training, 2019)
The purpose of this study was to examine the effect of place-based education integrated project studies on students’ problem solving and social skills. The participants were 18 (10 females and 8 males) 7th grade students located in a northeastern city of Turkey in the 2017 fall semester. Students conducted project studies about local history, cultural, and socio-economic structure of their environments within the context of place-based education approach. To collect data, Social Skills Scale to measure social skill levels of students and Perception Scale for Problem Solving Skills to measure students’ problem solving skills were used as pre- and post-tests. Since the study was conducted with only experimental group, simple experimental design was utilized. To analyze data, SPSS package program was used. Wilcoxon signed tests were used to determine whether there was a significant difference between the pre- and post-tests mean scores of the students' problem solving and social skills. The results of the Wilcoxon signed tests revealed that students' problem solving and social skills post-test scores were significantly higher than their problem solving and social skills pre-test scores. Therefore, it can be suggested that project studies within the context of place-based education approach should be included in the teaching of different skills, values, and knowledge within the scope of social studies. For future research, it can be recommended to conduct research studies investigating the effects of project-based learning integrated project studies or activities on students’ skills including communication, social inclusion, observation, and inquiry skills in social studies.